Optical soliton solutions of the cubic-quintic non-linear Schrödinger's equation including an anti-cubic term. Issue 12 (12th July 2018) - Kaplan, Melike; Hosseini, Kamyar; Samadani, Farzan; Raza, Nauman
Abstract: A wide range of problems in different fields of the applied sciences especially non-linear optics is described by non-linear Schrödinger's equations (NLSEs). In the present paper, a specific type of NLSEs known as the cubic-quintic non-linear Schrödinger's equation including an anti-cubic term has been studied. The generalized Kudryashov method along with symbolic computation package has been exerted to carry out this objective. As a consequence, a series of optical soliton solutions have formally been retrieved. It is corroborated that the generalized form of Kudryashov method is a direct, effectual, and reliable technique to deal with various types of non-linear Schrödinger's equations.